TINDAKAN PREMANISME SEBAGAI TINDAKAN PIDANA DITINJAU DARI KITAB UNDANG-UNDANG HUKUM PIDANA DI KOTA SAMARINDA (POLSEKTA SUNGAI KUNJANG) - maswedi maswedi (Universitas 17 Agustus 1945 Samarinda, 2013)
ABSTRACTThe times in the era of globalization not only brings great influence on the state Inonesia but also have an impact on the development of society, behavioral, and cultural shifts in the community.Such a situation is aggravated by the state of the Indonesian economy is getting weaker and the population growth rate is faster and it is not accompanied by adequate job creation. Giving rise to behavior that deviates from the public spotlight one author is an act of thuggery.Act of thuggery continues to grow from year to year so that makes unrest in society, thuggery in Indonesia is increasing fertile because thuggery has entered into the layers of people's lives, for example thuggery much employed in the company to facilitate their efforts there is also thuggery employed by the government with an excuse to protect them from external parties. It is very tragic dikehidupan a society in which the position of the security apparatus is no longer an option for those who are looking for security, but as we all know that this thuggery actions deviate from the provisions of the law but it is increasingly difficult to eradicate thuggery as we saw with thuggery until now still continue to exist even tend to increase.Decisive action of the apparatus is desirable in order to create a safe and orderly community life of this thuggery disorder.